Analisis Pemberian Kredit Pada PT. Bank Sumut Pematangsiantar - Asmawati Halilah Damanik; Eve Ida Malau; Richard Berlien (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2020)
In granting credit, banks must pay attention to the principles of sound credit, including the risks that must be faced on loan repayments by customers/debtors. In a credit application, the PT. Bank Sumut Pematangsiantar Branch conducts an analysis first related to the precautionary principle, after the bank believes and trusts the customer's ability to return the borrowed funds then the credit can be disbursed. This research is a qualitative research. This research was conducted at PT. Bank Sumut Pematangsiantar Branch. This study uses the interview method. Interviews were conducted with the Head of Credit, Credit Analysis, Customer Service, and Customers of Bank Sumut Pematangsiantar Branch. Data collection techniques were obtained by conducting interviews and observation methods. The results of this study indicate that the evaluation of the provision of credit is appropriate and in accordance with the existing theoretical studies, and the procedure for granting credit is in accordance with the procedures applied to PT. Bank Sumut Pematangsiantar Branch. Keywords: Evaluation, Credit Granting Procedures, Credit Granting Principles